Outcome of Jensen Procedure for Complete Abducent Nerve Palsy in Tertiary Eye Hospital of Nepal - Joshi, Purushottam; Suwal, Rinkal; Shrestha, Pranav (Nepal Journal of Neuroscience, 2023)
Introduction: Jensen procedure is done for correcting large amount of esotropia and improving abduction in complete abducent nerve palsy. It is a modified form of transposition surgery where the superior, inferior, lateral rectus muscles are split longitudinally and their lateral halves are respectively joined to the superior halves and inferior halves of lateral rectus with non-absorbable sutures. The study was done to find the surgery outcome of Jensen Procedure in complete abducent nerve palsy. Methods and Materials: A retrospective study of complete abducent nerve palsy of greater than six months duration that underwent Jensen Procedure was performed. Preoperative deviation and postoperative deviation at six weeks and three months were measured and analyzed. Clinical photography and diplopia charting of each case was done before surgery, and postoperatively at three months follow up in all cardinal gazes. Results: Eight eyes of eight patients with the mean age 38.50 ± 22.32 years (16 - 83) underwent medial rectus recession with muscle union (Jensen’s) procedure. Three right eyes and five left eyes were operated. The preoperative esodeviation reduced from mean preoperative 74.37±28.21∆ (30 - 120∆) base out to mean post-operative 12±12.29∆ (-8 – 30∆) base out. The abduction deficit improved from mean preoperative -3.75 ± 0.46 (-4 to -3) to postoperative -1.87 ± 0.99 (-3 to 0). All cases were satisfied with their ocular alignment and cosmesis. Conclusion: The Jensen Procedure can successfully correct the large amount of deviation due to complete abducent nerve palsy with improvement in functionality, abduction deficit and cosmesis.